Holiday Price Rigidity and Cost of Price Adjustment - Daniel Levy; Georg Müller; Shantanu Dutta; Mark Bergen (Bar-Ilan University, Department of Economics, 2002)
Using unique retail and wholesale price data for 4,532 products carried by a major Mid-western grocery retailer, we find evidence of significant retail price rigidity during the Thanksgiving through Christmas holiday period relative to the rest of the year. We suggest that this pattern of holiday retail price rigidity is best explained by an increased opportunity cost of changing prices at these stores during the holiday period. Evidence based on discussions with retail managers suggests that during holidays the physical, managerial, and customer costs of changing prices rise considerably. Due to higher store traffic, performing tasks such as restocking shelves, handling customers' questions and inquiries, running cash registers, cleaning, and bagging, become more urgent during holidays and thus receive priority. As a result, the holiday-period opportunity cost of price adjustment increases dramatically for the stores. The data provide a natural experimental setting to study variation in price rigidity because the products, stores, and surrounding institutional features and arrangements, including the market structure, the contractual arrangements, and the nature of relationships, etc., do not change between holiday and non-holiday weeks.
Keywords: E12; E31; 330; price rigidity; costs of price adjustment; holidays